(untitled) (REMUNOM, 2024)
The rehabilitation of teeth with major coronal destruction presents significant challenges in contemporary dental practice, requiring a careful and multidisciplinary approach to achieve satisfactory results. This scientific article fundamentally examines the challenges inherent to this process, with a special focus on the use of intraradicular retainers as a possible solution to guarantee stability and longevity of restorations. The complexities associated with preserving the remaining tooth structure, obtaining adequate retention, and preventing secondary complications in cases of major coronal destruction were discussed. Next, the implications of using intraradicular retainers were explored, considering the potential benefits in terms of mechanical stability and retention of the restoration, as well as the associated challenges and risks, such as compromising pulp vitality and difficulty in future removal. Through a comprehensive review of up-to-date scientific literature and analysis of relevant clinical cases, this article offers valuable insights for dental professionals, highlighting the importance of a personalized and integrated approach in the rehabilitation of teeth with major coronal destruction. By carefully weighing the benefits and risks of using intraradicular retainers, professionals can make informed and effective decisions to provide aesthetic, functional and long-lasting results for their patients.